Q-switched ytterbium-doped fiber laser via a thulium-doped fiber saturable absorber - Rahman, Mohd Fauzi Ab; Latiff, Anas Abdul; Rusdi, Muhammad Farid Mohd; Dimyati, Kaharudin; Harun, Sulaiman Wadi (Optical Society of America, 2018)
We demonstrated a reliable and stable Q-switched ytterbium-doped fiber laser centered at 1069 nm by employing a segment of 11 cm thulium-doped fiber (TDF) as a saturable absorber (SA) in the ring cavity. The fiber SA has an optical absorption of 1.35 dB at the Q-switched operating regime. As we increased the pump power from 109 mW to the maximum available pump power of 206 mW, a consistent Q-switched laser with output power ranging from 1.8 to 4.8 mW was attained. The pulse width narrowed from 4.9 to 2.87 μs, whereas the repetition rate increased from 40 to 60.2 kHz. In addition, maximum pulse energy of 80.7 nJ and a maximum peak power of 28.1 mW were obtained at the maximum pump power. The signal to noise ratio (SNR) was around 47 dB. Our experimental study shows that a segment of TDF can be used as a Q-switcher in the 1 μm fiber laser cavity to facilitate a reliable and robust microsecond pulse generation.